(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2019)
The prison system has an information regime that is composed of elements that determine the flow of information in a given social and / or informational space. The purpose of this article is to study the conditions of information mediation in remission of sentence by reading in the context of the regime (s) of information of the criminal types in the Brazilian Prison System. The Brazilian Penal Code is organized in titles, chapters and, if necessary, sections. Although the mediator of a reading remission project does not need to know all the existing criminal types, he must consider them in the conduct of the community study.